IZIN MENGEMUDI TRANSPORTASI AIR DIKECAMATAN LEDO - KARDINA SOPIANA NIM. A1011181008 (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstract Transportation is one of the facilities used by the community to reach from one place to another. Transportation itself is also commonly defined as a process, namely the process of moving, moving, and transporting, and diverting where this process cannot be separated from the need for supporting tools to ensure a smooth transfer process in accordance with the desired time. Transportation is meant not only land transportation but also water transportation. Where not all destinations can be easily reached by land, especially in the Ledo District, Bengkayang Regency. then water transportation is the solution. The demand for transportation services that is not accompanied by the provision of proper transportation services will hamper the mobility of the community in meeting their daily needs. Seeing this condition, water transportation entrepreneurs in Ledo District in particular offer shipping services using boats as a means of transportation. Water transportation entrepreneurs can operate smoothly without any problems even though almost all of the drivers do not have operational permits or shipworthiness certificates (SKK).Therefore, the authors are interested in researching with the formulation of the problem, namely why the implementation of a water transportation driving license in Ledo sub-district has not been implemented effectively. The method used is the empirical legal method and normative law, which is a legal method that functions to see the law in a real sense and examines how the law works in the community and finds the truth based on scientific logic from the normative side. The data analysis used in this research is descriptive analysis.The factor that causes water transportation entrepreneurs not to fulfill their obligations is because there is no local government policy in Bengkayang Regency, in this case the Department of Transportation, which regulates the mechanisms and procedures for licensing river and lake crossings in the field of water transportation, thus preventing the fulfillment of requirements to have a shipworthiness certificate (SKK), which must first have an operational permit issued by the Regional Government, especially the Bengkayang Transportation Service.Key Word : Transportation, Type Of Transportation, Seaworthiness Certificate (SC). Abstrak Transportasi merupakan salah satu sarana yang digunakan masyarakat untuk menjangkau dari satu tempat ke tempat lainnya. Transportasi itu sendiri juga biasa diartikan sebagai sebuah proses, yakni proses pemindahan, pergerakan, dan pengangkutan, serta mengalihkan dimana proses ini tidak bisa dilepaskan dari keperluan akan alat pendukung untuk menjamin lancarnya proses perpindahan sesuai dengan waktu yang diinginkan. Transportasi yang di maksud bukan hanya transportasi darat melainkan juga transportasi air. Dimana tidak semua tempat tujuan dapat dijangkau dengan mudah melalui daratan, khususnya di daerah Kecamatan Ledo Kabupaten Bengkayang. maka transportasi air menjadi solusinya. Permintaan akan layanan jasa transportasi yang tidak diiringi dengan penyediaan layanan jasa transportasi yang layak akan menghambat mobilitas masyarakat dalam memenuhi kebutuhan hidupnya. Melihat kondisi ini, para pengusaha transportasi air di Kecamatan Ledo khususnya menawarkan jasa pelayaran menggunakan perahu sebagai sarana transportasi. Pengusaha transportasi air dapat beroperasi dengan lancar tanpa kendala padahal hampir dari semua pengemudinya tidak mengantongi surat izin operasional maupun sertifikat kelaikan kapal (SKK).Oleh karena itu, penulis tertarik untuk meneliti dengan rumusan masalah yaitu mengapa pelaksanaan surat izin mengemudi transportasi air di kecamatan ledo belum terlaksana secara efektif. Metode yang digunakan adalah metode hukum empiris dan hukum normatif yaitu suatu metode hukum yang berfungsi untuk melihat hukum dalam artian nyata dan meneliti bagaimana bekerjanya hukum di lingkungan masyarakat dan menemukan kebenaran berdasarkan logika keilmuan dari sisi normatifnya. Analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif.Faktor yang menyebabkan pengusaha transportasi air tidak memenuhi kewajibannya adalah karena tidak adanya kebijakan pemerintah daerah Kabupaten Bengkayang dalam hal ini Dinas Perhubungan yang mengatur mengenai mekanisme dan prosedur perizinan penyeberangan sungai dan danau di bidang transportasi air, sehingga menyebabkan tidak bisa terpenuhinya syarat untuk memiliki sertifikat kelaikan kapal (SKK), yaitu harus memiliki surat izin operasional terlebih dahulu yang dikeluarkan oleh Pemerintahan Daerah khususnya Dinas Perhubungan Bengkayang.Kata Kunci: Transportasi, Jenis Transportasi, Sertifikat Kelaikan Laut (SKK).